Potashchelins, a Suite of Lipid Siderophores Bearing Both L-threo and L-erythro Beta-Hydroxyaspartic Acids, Acquired From the Potash-Salt-Ore-Derived Extremophile Halomonas sp. MG34 - Li, Yihong; Liu, Li; Zhang, Gengxin; He, Ning; Guo, Wenqiang; Hong, Bin; Xie, Yunying (Frontiers in Chemistry, 2020)
Four new lipid siderophores bearing both L-threo- and L-erythro-β-hydroxyaspartic acids, potashchelins A-D (1-4), were isolated from the potash-salt-ore-derived extremophile Halomonas sp. MG34. The planar structures of 1-4 were elucidated on the basis of extensive 1D and 2D NMR studies and MS/MS data. Potashchelins 1-4 contain a hydrophilic nonapeptide headgroup sequentially consisting of β-hydroxyaspartic acid, serine, glycine, serine, serine, β-hydroxyaspartic acid, threonine, serine, and cyclic N(δ)-hydroxy-ornithine, which is appended by one of a series of fatty acids ranging from dodecanoic acid to tetradecanoic acid. The absolute configurations of the amino acids of potashchelins 1-4 were determined by C3 and advanced Marfey's reaction, partial hydrolysis, and bioinformatics analysis, which revealed that potashchelins 1-4 bear both L-threo- and L-erythro-β-hydroxyaspartic acid. Phylogenetic analysis showed that the stand-alone β-hydroxylase, PtcA, and the fused domain with β-hydroxylase activity in PtcB are expected to be responsible for the formation of L-erythro and L-threo diastereomers, respectively. Additionally, utilizing a comparative genomics approach, we revealed an evolutionary mechanism for lipid siderophores in Halomonas involving horizontal transfer. Bioassays showed that potashchelin A and D had weak antibacterial activity against B. subtilis CPCC 100029 with an MIC value of 64 μg/mL.